Plasma taurine levels are not affected by vigabatrin in pediatric patients. (26th June 2016) - Spelbrink, Emily M.; Mabud, Tarub S.; Reimer, Richard; Porter, Brenda E.
Summary: Vigabatrin is a highly effective antiseizure medication, but its use is limited due to concerns about retinal toxicity. One proposed mechanism for this toxicity is vigabatrin‐mediated reduction of taurine. Herein we assess plasma taurine levels in a retrospective cohort of children with epilepsy, including a subset receiving vigabatrin. All children who underwent a plasma amino acid analysis as part of their clinical evaluation between 2006 and 2015 at Stanford Children's Health were included in the analysis. There were no significant differences in plasma taurine levels between children taking vigabatrin (n = 16), children taking other anti‐seizure medications, and children not taking any anti‐seizure medication (n = 556) (analysis of variance [ANOVA] p = 0.841). There were, however, age‐dependent decreases in plasma taurine levels. Multiple linear regression revealed no significant association between vigabatrin use and plasma taurine level (p = 0.87) when controlling for age. These results suggest that children taking vigabatrin maintain normal plasma taurine levels, although they leave unanswered whether taurine supplementation is necessary or sufficient to prevent vigabatrin‐associated visual field loss. They also indicate that age should be taken into consideration when evaluating taurine levels in young children.